Hubungan Kepatuhan Minum Obat Antihipertensi Terhadap Kualitas Hidup Pada Pasien Hipertensi Di Provinsi Jawa Tengah - Dedy Frianto; Annisa Fitriyani; Dinda Dinanti; Kartika Sari; Maulida Mutiah; Muhammad Zein (Journal of Pharmaceutical and Sciences, 2023)
Basically the purpose of this study was to observe the description of adherence to taking antihypertensive medication with quality of life in hypertensive patients in Central Java Province. The method used in this study is a quantitative method with a cross sectional design. Data were obtained by using a knowledge questionnaire for antihypertensive treatment and the "Morisky Medication Adherence Scales-8" (MMAS-8) scale with a total sample selected by accidental sampling of 77 hypertensive patients. From the results of the study of 77 samples, it was shown that there was a significant relationship between the level of knowledge of hypertensive patients and patient adherence in taking antihypertensive drugs (p-value = 0.01). So that the results of this study can be used as a guideline for health workers, especially nurses, so that they can provide even better education. Thus, if the education is carried out properly, the adherence to taking medication for hypertensive patients is expected to increase so that it can have a better influence on the patient's quality of life